EFFECTS OF COGNITIVE LOAD AND PASSWORD STRENGTH ON STUDENT PRODUCTIVITY (Contemporary Journal of Social Science Review, 2023)
In recent decades, the complexity of information systems (IS) has grown, necessitating robust system authentication methods. While passwords remain a common choice, they often encounter issues related to security. Businesses are increasingly mandating the use of intricate and frequently changed passwords to address these concerns. However, this approach can lead to challenges for users, particularly students, as their cognitive load escalates due to the demanding nature of such passwords. This study delved into the impact of heightened password complexity on users' cognitive load during the login process, ultimately identifying the threshold at which password strength begins to affect end-user performance. By investigating the gradual elevation of cognitive load through varied password strengths, this research aimed to shed light on the interplay between independent variables like cognitive load and password strength and their influence on the dependent variable of student productivity. Surprisingly, the study found that neither cognitive load nor password strength significantly affected the factors under examination. On the other hand, age and gender emerged as significant determinants, while computer usage displayed no statistically significant impact. These findings contribute valuable insights into user behavior within the realm of information security, offering a more comprehensive understanding of the dynamics at play in this context.